2008
DOI: 10.1016/j.ydbio.2008.02.035
|View full text |Cite
|
Sign up to set email alerts
|

Sox2 is important for two crucial processes in lung development: Branching morphogenesis and epithelial cell differentiation

Abstract: The primary lung bud originates from the foregut and develops into the bronchial tree by repetitive branching and outgrowing of the airway. The Sry related HMG box protein Sox2 is expressed in a cyclic manner during initiation and branching morphogenesis of the lung. It is highly expressed in non-branching regions and absent from branching regions, suggesting that downregulation of Sox2 is mandatory for airway epithelium to respond to branch inducing signals. Therefore, we developed transgenic mice that expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
254
1
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 245 publications
(265 citation statements)
references
References 59 publications
8
254
1
2
Order By: Relevance
“…In support of this, SOX2 proved to be significantly co-expressed with typical markers of squamous cell carcinoma differentiation, such as p63. 9,15,25 Besides the lung, SOX2 has been found to be amplified and expressed in squamous cell carcinomas originating from other organ sites, predominantly derived from the embryonic foregut. 9,21,22 Recently, we found SOX2 to be amplified and expressed in squamous cell carcinomas originating from non-foregut tissues, such as the skin, the cervix, and the penis, 23 indicating that SOX2 might be a general marker for squamous cell carcinoma differentiation regardless the tissue of origin.…”
Section: Sox2 In Squamous Cell Carcinomas From Other Organ Sitesmentioning
confidence: 99%
See 2 more Smart Citations
“…In support of this, SOX2 proved to be significantly co-expressed with typical markers of squamous cell carcinoma differentiation, such as p63. 9,15,25 Besides the lung, SOX2 has been found to be amplified and expressed in squamous cell carcinomas originating from other organ sites, predominantly derived from the embryonic foregut. 9,21,22 Recently, we found SOX2 to be amplified and expressed in squamous cell carcinomas originating from non-foregut tissues, such as the skin, the cervix, and the penis, 23 indicating that SOX2 might be a general marker for squamous cell carcinoma differentiation regardless the tissue of origin.…”
Section: Sox2 In Squamous Cell Carcinomas From Other Organ Sitesmentioning
confidence: 99%
“…High SOX2 expression is found in all endoderm cells of the undivided foregut with protein levels being higher in the dorsal foregut (the future esophagus) and lower in the ventral foregut (the future trachea). 15,16 During bronchogenesis in the developing lung, SOX2 is precisely regulated and forced overexpression of SOX2 leads to a block of airway branching. 15 In the adult, SOX2 expression is found in the basal cell layer of the esophagus and in bronchial epithelial cells of the lung, whereas it is absent in alveolar cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…SOX2 is also expressed in the developing respiratory epithelium and is restricted to conducting airways of the mature lung (19). SOX2 is induced in the bronchiolar epithelium during repair after toxicant-induced injury (20).…”
Section: Expression Of Met and Sox2 Genes In Non-small Cell Lung Carcmentioning
confidence: 99%
“…SOX2 is induced in the bronchiolar epithelium during repair after toxicant-induced injury (20). Overexpression of SOX2 in lung epithelium during early development disrupted branching morphogenesis, causing cystic lungs and neonatal death (19). It has been suggested that SOX2, which belongs to group B of the SOX family plays critical roles in cell fate determination, differentiation and proliferation (21,22).…”
Section: Expression Of Met and Sox2 Genes In Non-small Cell Lung Carcmentioning
confidence: 99%